2014
DOI: 10.1016/j.ijrobp.2014.04.041
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Hyperfractionation Versus Conventional Fractionation in T2 Squamous Cell Carcinoma of the Vocal Cord (RTOG 9512)

Abstract: Purpose To compare hyperfractionation versus standard fractionation for T2N0 vocal cord carcinoma in a randomized controlled trial. Methods and Materials Patients with T2 vocal cord cancer were stratified by substage (T2a vs. T2b) and randomly assigned to receive either hyperfractionation (HFX) to 79.2 Gy in 66 fractions of 1.2 Gy given twice a day, or standard fractionation (SFX) to 70 Gy in 35 fractions given once a day. The trial was designed to detect a 55% reduction in the local failure hazard rate with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
49
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 20 publications
(22 reference statements)
1
49
1
1
Order By: Relevance
“…The control group of a four-arm trial 4 was triplicated (ie, data for patients in the control group were copied twice to have three control arms to compare with each experimental arm), a 2 × 2 trial (EORTC 22962 45 ) included three relevant comparisons for the meta-analysis, and three three-arm trials 36,37,55 included two relevant comparisons. The 33 trials included in the analysis of fractionation schedules (comparison 1) were divided into four predefined subgroups, depending on the type of radiotherapy: hyperfractionation (eight comparisons, including the unpublished EORTC 22962 trial), 4,33,44,45,49,50,56 moderately accelerated radiotherapy (19 comparisons), 2,4,30,32,3439,41,42,46,54,55,5759 very accelerated radiotherapy (seven comparisons, including the unpublished CHARTWEL trial), 3,47,5153,60 and moderately hypofractionated (dose per fraction between 2–2·5 Gy [two comparisons]; 31,40 appendix pp 17–18). After discussion with the steering committee, the moderately hypofractionated trials were included in the moderately accelerated radiotherapy group.…”
Section: Resultsmentioning
confidence: 99%
“…The control group of a four-arm trial 4 was triplicated (ie, data for patients in the control group were copied twice to have three control arms to compare with each experimental arm), a 2 × 2 trial (EORTC 22962 45 ) included three relevant comparisons for the meta-analysis, and three three-arm trials 36,37,55 included two relevant comparisons. The 33 trials included in the analysis of fractionation schedules (comparison 1) were divided into four predefined subgroups, depending on the type of radiotherapy: hyperfractionation (eight comparisons, including the unpublished EORTC 22962 trial), 4,33,44,45,49,50,56 moderately accelerated radiotherapy (19 comparisons), 2,4,30,32,3439,41,42,46,54,55,5759 very accelerated radiotherapy (seven comparisons, including the unpublished CHARTWEL trial), 3,47,5153,60 and moderately hypofractionated (dose per fraction between 2–2·5 Gy [two comparisons]; 31,40 appendix pp 17–18). After discussion with the steering committee, the moderately hypofractionated trials were included in the moderately accelerated radiotherapy group.…”
Section: Resultsmentioning
confidence: 99%
“…A similar Korean trial of 156 patients with T1-T2 glottic scc substantiated the finding of improved disease control after accelerated hypofractionated radiotherapy compared to conventional fractionated radiotherapy [19]. In the RTOG 9512 study hyperfractionation with a 9.2 Gy dose increase and 0.5 week treatment time reduction increased local control 8% (78% vs 70%, p > 0.05) in T2N0 glottic cancer patients compared to conventional RT [20]. Overall, the evidence of a positive effect of reduced treatment time on loco-regional control is convincing.…”
Section: Discussionmentioning
confidence: 71%
“…Several randomized studies have evaluated altered fractionation via gentle hypofractionation 17,18 or hyperfractionation 19 as a means to improve local tumor control in early-stage laryngeal cancer. All three studies demonstrated at least a trend favoring altered fractionation.…”
Section: Resultsmentioning
confidence: 99%